REGULASI DIRI DAN PROKRASTINASI AKADEMIK PADA MAHASISWA ANGGOTA PADUAN SUARA - Wowor, Marcell Devano Rangga; Wibowo, Doddy Hendro (Prodi Psikologi- Fakultas Psikologi & Humaniora - Universitas Teknologi Sumbawa, 2025)
Academic procrastination among university students is influenced by several factors, one of which is self-regulation. This study aims to analyze the relationship between self-regulation and academic procrastination among university students who are members of a choir. Using a quantitative approach with accidental sampling, 123 choir group students were selected as participants. Data were collected using the Self-Regulated Learning Scale and the Procrastination Assessment Scale for Students (PASS), then analyzed with the Pearson product-moment correlation test. Results showed a positive correlation of 0.589 with a significance value of 0.000 (p < 0.05), indicating a significant positive relationship between self-regulation and academic procrastination. This finding contradicts previous studies that reported a negative correlation between the two variables. The implication suggests that self-regulation does not always serve as a protective factor against academic procrastination, especially among students involved in choir activities.